Invasion Science: A Horizon Scan of Emerging Challenges and Opportunities - Ricciardi, Anthony; Blackburn, Tim M; Carlton, James T; Dick, Jaimie T A; Hulme, Philip E; Iacarella, Josephine C; Jeschke, Jonathan M; Liebhold, Andrew M; Lockwood, Julie L; MacIsaac, Hugh J; Pyšek, Petr; Richardson, David M; et al. (Trends in ecology & evolution, 2017)
We identified emerging scientific, technological, and sociopolitical issues likely to affect how biological invasions are studied and managed over the next two decades. Issues were ranked according to their probability of emergence, pervasiveness, potential impact, and novelty. Top-ranked issues include the application of genomic modification tools to control invasions, effects of Arctic globalization on invasion risk in the Northern Hemisphere, commercial use of microbes to facilitate crop production, the emergence of invasive microbial pathogens, and the fate of intercontinental trade agreements. These diverse issues suggest an expanding interdisciplinary role for invasion science in biosecurity and ecosystem management, burgeoning applications of biotechnology in alien species detection and control, and new frontiers in the microbial ecology of invasions.
Keywords: global change; invasive species; microbial ecology; ekosystém; zavlečené druhy; Ecosystem; Introduced Species; rapid evolution; Arctic globalization; gene drives